Efektivitas Penertiban Parkir Liar di Kawasan Obyek Wisata Ubud - Pande Putu Gede Parwata; Ida Ayu Putu Widiati; I Wayan Artanaya (Jurnal Konstruksi Hukum, 2021)
The problem of illegal parking that occurs in the tourist area of ​​Ubud has prompted the Gianyar Regency Government to issue a Gianyar Regent Regulation Number 57 of 2018 concerning the Management and Engineering of Traffic and Road Transportation and Parking in the Ubud Tourism Area. This study aims to determine the effectiveness of the Gianyar Regent Regulation Number 57 of 2018 concerning the Management and Engineering of Traffic and Road Transportation and Parking in the Ubud Tourism Area and to determine the application of sanctions against illegal parking prohibitions in the Ubud Tourism Object area. This research is an empirical legal research. The approach to the problem used is the sociology of law approach. Based on the results of the study, the parked vehicles are not properly organized due to the lack of parking arrangements that occur in the tourist area of ​​Ubud. The application of sanctions against the prohibition of illegal parking in the tourist area of ​​Ubud is carried out, starting from giving warnings for breaking tires, towing the transportation of violating vehicles to tickets. Thus, law enforcement officers should be more assertive in effectively implementing the prohibition on illegal parking on the shoulder of the Ubud road area. The road user community should be pro-active towards the applicable regulations. People who obey the rules should not only be there when there are traffic officers, but also obey the rules when there is no guard.